Scatter Reduction and Correction for Dual-Source Cone-Beam CT Using Prepatient Grids. (June 2016) - Ren, Lei; Chen, Yingxuan; Zhang, You; Giles, William; Jin, Jianyue; Yin, Fang-Fang
Purpose: Scatter significantly limits the application of the dual-source cone-beam computed tomography by inducing scatter artifacts and degrading contrast-to-noise ratio, Hounsfield-unit accuracy, and image uniformity. Although our previously developed interleaved acquisition mode addressed the cross scatter between the 2 X-ray sources, it doubles the scanning time and doesn't address the forward scatter issue. This study aims to develop a prepatient grid system to address both forward scatter and cross scatter in the dual-source cone-beam computed tomography. Methods: Grids attached to both X-ray sources provide physical scatter reduction during the image acquisition. Image data were measured in the unblocked region, while both forward scatter and cross scatter were measured in the blocked region of the projection for postscan scatter correction. Complementary projections were acquired with grids at complementary locations and were merged to form complete projections for reconstruction. Experiments were conducted with different phantom sizes, grid blocking ratios, image acquisition modes, and reconstruction algorithms to investigate their effects on the scatter reduction and correction. The image quality improvement by the prepatient grids was evaluated both qualitatively through the artifact reduction and quantitatively through contrast-to-noise ratio, Hounsfield-unit accuracy, and uniformity using a CATphan 504 phantom. Results: Scatter artifacts were reduced by scatter reduction and were removed by scatter correction method. Contrast-to-noise ratio, Hounsfield-unit accuracy, and image uniformity were improved substantially. The simultaneous acquisition mode achieved comparable contrast-to-noise ratio as the interleaved and sequential modes after scatter reduction and correction. Higher grid blocking ratio and smaller phantom size led to higher contrast-to-noise ratio for the simultaneous mode. The iterative reconstruction with total variation regularization was more effective than the Feldkamp, Davis, and Kress method in reducing noise caused by the scatter correction to enhance contrast-to-noise ratio. Conclusion: The prepatient grid system is effective in removing the scatter effects in the simultaneous acquisition mode of the dual-source cone-beam computed tomography, which is useful for scanning time reduction or dual energy imaging.